2012
DOI: 10.1051/0004-6361/201219912
|View full text |Cite
|
Sign up to set email alerts
|

The complete far-infrared and submillimeter spectrum of the Class 0 protostar Serpens SMM1 obtained withHerschel

Abstract: We present the first complete ∼55−671 μm spectral scan of a low-mass Class 0 protostar (Serpens SMM1) taken with the PACS and SPIRE spectrometers onboard Herschel. More than 145 lines have been detected, most of them rotationally excited lines of 12 CO (full ladder from J u = 4−3 to 42−41 and E u /k = 4971 K), H 2 O (up to 8 18 −7 07 and E u /k = 1036 K), OH (up to 2 Π 1/2 J = 7/2−5/2 and E u /k = 618 K), 13

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
166
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 90 publications
(189 citation statements)
references
References 60 publications
(108 reference statements)
22
166
0
1
Order By: Relevance
“…Neufeld (2012) has demonstrated that the excitation pattern of CO at a single kinetic temperature shows a broken power-law pattern that can reproduce the observed A88, page 10 of 22 distribution at sufficiently high temperatures and for densities below the critical density. This possibility has been examined for SMM1 in Serpens and B335, which display a similar excitation pattern to the Serpens sources of this work (Goicoechea et al 2012;Green et al 2013, respectively). In both cases, they find that solutions can be obtained for n(H 2 ) = 10 4 cm −3 and T ∼ 3000 K. While low densities are predicted by shock models (Sect.…”
Section: Excitation Conditionsmentioning
confidence: 62%
See 1 more Smart Citation
“…Neufeld (2012) has demonstrated that the excitation pattern of CO at a single kinetic temperature shows a broken power-law pattern that can reproduce the observed A88, page 10 of 22 distribution at sufficiently high temperatures and for densities below the critical density. This possibility has been examined for SMM1 in Serpens and B335, which display a similar excitation pattern to the Serpens sources of this work (Goicoechea et al 2012;Green et al 2013, respectively). In both cases, they find that solutions can be obtained for n(H 2 ) = 10 4 cm −3 and T ∼ 3000 K. While low densities are predicted by shock models (Sect.…”
Section: Excitation Conditionsmentioning
confidence: 62%
“…Reported column densities are about 2 orders of magnitude higher for both the warm and hot components in SMM1 than corresponding ones reported here. This difference can be interpreted in terms of the smaller emitting area of 4 assumed in Goicoechea et al (2012) and the estimating method, which is based on non-LTE analysis. The CO column density ratio of the hot and warm components in both studies is ∼20, indicating that the relative contribution of the two components remains invariable despite the different approaches.…”
Section: Position T 1 (K)mentioning
confidence: 99%
“…Figure 8 presents the excitation diagram built from our best-fit model for CO. As extensively described in Goldsmith & Langer (1999), in local thermodynamical equilibrium conditions and under optically thin regime, the points in this type of diagram are expected to fall on a straight line, whose inverse of the slope is the excitation temperature of the transitions (also see the description of H 2 excitation diagrams in Sect. 4.1).…”
Section: Employing Shock Models: Energeticsmentioning
confidence: 90%
“…The Heterodyne Instrument for Far-Infrared (HIFI; de Graauw et al 2010) on Herschel offers a unique opportunity to observe spectrally resolved high-J CO lines of various isotopologs with unprecendented sensitivity (see Yıldız et al 2010;Plume et al 2012, for early results). Even higher transitions of CO up to J u = 50 are now routinely observed with the Photoconducting Array and Spectrometer (PACS; Poglitsch et al 2010) and the Spectral and Photometric Imaging Receiver (SPIRE; Griffin et al 2010) instruments on Herschel, but those data are spectrally unresolved, detect mostly 12 CO, and probe primarily a hot shocked gas component associated with the source (e.g., van Kempen et al 2010;Herczeg et al 2012;Goicoechea et al 2012;Karska et al 2013;Manoj et al 2013;Green et al 2013). To study the bulk of the protostellar system and disentangle the various physical components, velocity resolved lines of isotopologs including optically thin C 18 O are needed.…”
Section: Introductionmentioning
confidence: 99%